Teachers' Knowledge and Preparedness for Retirement: Results From a Nationally Representative Teacher Survey - Dillon Fuchsman; Josh B. McGee; Gema Zamarro (SAGE Publishing, 2024)
Adequately preparing for retirement requires planning and knowledge about available savings and investment options. Teachers participate in a complex set of plan designs, and many do not participate in Social Security. While teachers represent a large part of the public workforce, relatively little is known regarding their knowledge and preparation for retirement. We administered a survey to a nationally representative sample of teachers through RAND's American Teacher Panel and asked teachers about their retirement planning and employer-sponsored retirement plans. We find that while most teachers are taking steps to prepare for retirement, many teachers do not currently possess the basic retirement knowledge necessary to plan effectively. Teachers struggled to identify their plan type, how much they contribute to their plans, retirement eligibility ages, and who contributes to Social Security. These results suggest that better education around teacher retirement plans has the potential to improve teachers' retirement planning and preparation.